Adapting to the Land : A History of Agriculture in Colorado - Freeman, John F. (John Francis), 1940-; Uchanski, Mark E., 1980- (Book collections on Project MUSE., 2021)
"Examines how Colorado agriculturists, from the Ancestral Puebloans to twenty-first-century ranchers and farmers, have adapted to and sought to overcome the natural limits of land and water. Documents the state's farming history and provides context for significant methodological and ideological transformations, including the organic, local foods movement."--